Pengendalian Sudut Pitch dan Roll Pesawat Flying Wing - Susanto, Try (Jurnal Teknologi Elektro, 2022)
The development of the aviation world in recent years has increased, one of which is the field of unmanned aerial vehicles. This development is in line with the increasing use of UAVs in various fields, including for military missions, natural disaster monitoring missions, and aerial photography missions. Many types of aircraft that can be used to complete these missions, one type of aircraft that is widely used is the flying wing type aircraft. This type of aircraft is triangular in shape and does not have a tail. This aircraft controller uses elevons on the right and left sides of its wings, and its form is relatively small, so this aircraft is susceptible to environmental disturbances and causes flight mission failures. To overcome this problem, a control system is needed that is able to make the aircraft maintain flight stability. In this study, the Linear Quadratic Regulator control method was applied to overcome this. The LQR control method is used to control the pitch and roll angles of the aircraft. Based on the test results, the interference given can be handled well by the aircraft. It was proven that when given a disturbance, the aircraft experienced an overshoot of 4.24º at the pitch angle and 4.26º at the roll angle, but could quickly return to the setpoint within 1.2 seconds at the pitch angle, and 1.3 seconds at the roll angle. Thus the aircraft is able to maintain flight stability.